“THE DIRECTION OF THE WHOLE OF THE FORCES AVAILABLE”: THE DISPUTED SPHERES OF MILITARY AND CIVIL AUTHORITY IN THE EASTERN CAPE (1877– 1878), NATAL (1879) AND ZULULAND (1888) - Laband, John (Scientia Militaria - South African Journal of Military Studies, 2013)
In the late Victorian British Empire, the spheres of authority of the civil andmilitary powers were not unequivocally defined, and could lead to wrangles thatthreatened the efficient conduct of military operations. Three such disputes occurredin southern Africa between 1878 and 1888. In 1878, during the 9th Cape FrontierWar, the high commissioner replaced the Cape ministry with a more compliant oneto assert control over both the imperial and colonial forces engaged. During theAnglo-Zulu War of 1879, the lieutenant-governor of Natal disputed the right of thegeneral officer commanding to deploy African levies raised and stationed in Natalalong the Zululand border. In 1888, during the uSuthu Rebellion in Zululand, thegovernor interfered with the general’s military arrangements because he believedthese arrangements affected his civil powers. To head off future disputes of thisnature, the British government ruled in 1879 that the commander in the field alwayshad to exercise full control over active operations, and in 1888 finally clarified inwhich circumstances the general in command assumed operational authority overboth the colonial and imperial troops stationed in a colony.